Visual and Verbal Sign in RM and Wale Music Video “Change” - Salsabila Husna Ramadhani Amara; Made Budiarsa; Gede Primahadi Wijaya Rajeg (Research and Community Services Institutes of Udayana University, 2022)
The writing of “Visual and Verbal Signs in RM and Wale Music Video Change” is to identify the types of visual communication elements and to analyze the meaning in visual and verbal communication elements. The data was collected by documentation method, note-taking technique and by downloading the music video, watching and listening carefully and finding the signs and classifying the data according to the types. In analyzing the data, the theory of visual communication proposed by Dyer (1993) and theory types of meaning proposed by Leech (1983) were used. The finding of analysis shows 15 elements in six visual categories. They include appearance (age, gender, national & racial, hair, body & size, look), manner (expression, eye contact, pose, & clothes), activity (touch, body movement, positional communication), props and setting. While in verbal representation of the Change music video clip findings seven meanings including conceptual meaning, connotative meaning, social meaning, affective meaning, reflected meaning, collocative meaning and thematic meaning.